2007
DOI: 10.1002/mrd.20796
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of leptin and its receptor expression in mouse testis during the postnatal period

Abstract: The mechanism by which leptin regulate male reproductive development during postnatal periods remain to be determined. Using immunohistochemistry and reverse transcription-polymerase chain reaction (RT-PCR), we established that leptin is expressed in mouse testis with a cell-type and stagedependent manner during the postnatal period. In testes of 5-day-old mice, leptin expression was mainly restricted to gonocytes, whereas the immunostaining of leptin was confined to spermatogonia in 10-day-old testes. From Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 46 publications
(68 reference statements)
1
32
0
1
Order By: Relevance
“…In fact, in the rat, leptin was expressed in seminiferous tubules and in the interstitium of the adult gonads (Chen et al, 2008), whereas Ob-R was confined only in the Leydig cells of mature testes (Caprio et al, 2003), but it was absent in immature gonads. In contrast, in the mouse, leptin and its receptor were detected exclusively in germ cells of immature and mature testes (El-Hefnawy et al, 2000;Herrid et al, 2008). Furthermore, in the human adult testes, leptin was found in seminiferous tubules, whereas Ob-R was detected in Leydig cells (Glander et al, 2002;Soyupek et al, 2005;Ishikawa et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In fact, in the rat, leptin was expressed in seminiferous tubules and in the interstitium of the adult gonads (Chen et al, 2008), whereas Ob-R was confined only in the Leydig cells of mature testes (Caprio et al, 2003), but it was absent in immature gonads. In contrast, in the mouse, leptin and its receptor were detected exclusively in germ cells of immature and mature testes (El-Hefnawy et al, 2000;Herrid et al, 2008). Furthermore, in the human adult testes, leptin was found in seminiferous tubules, whereas Ob-R was detected in Leydig cells (Glander et al, 2002;Soyupek et al, 2005;Ishikawa et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…In fact, Lep and/or Ob-R were detected in rodent testes (Caprio et al, 2003;El-Hefnawy et al, 2000;Herrid et al, 2008), in human testes and seminal plasma (Glander et al, 2002;Soyupek et al, 2005;Ishikawa et al, 2007), in human sperm (Aquila et al, 2005), in boar sperm (De Ambrogi et al, 2007), and in pig sperm (Aquila et al, 2008). Furthermore, a recent paper reported the effects of leptin treatment, alone or in combination with dietary energy restriction, on different reproductive parameters of male rats (Sirotkin et al, 2008).…”
mentioning
confidence: 99%
“…35 Besides the hormonal profile, the lack of information about the morphofunctional analysis of the obese Zucker rat testis has propelled us toward this investigation. Along with its primary actions at the hypothalamic-pituitary level, leptin has direct effects on the proliferation, differentiation of germ cells, and modulation of testicular steroidogenesis, using both autocrine and paracrine mechanisms 36 that can utterly affect the reproductive function. Some reports have already showed that the obese Zucker rats present alterations in some reproductive organ weights, 14,15,35 which could be caused by the lack of leptin stimulus 32 ; however, the study presented here is the first to evaluate the testicular histological characteristics and sperm production in the pubertal phase of the Zucker rat as well as its effects on DNA integrity in its sexual maturity.…”
Section: Short Arrows) Surrounded By Sertoli Cells (Long Arrows) In mentioning
confidence: 99%
“…So, it seems leptin mainly acts through endocrine mechanism in cattle. However, recent publications in other species have been reported that leptin also present in some other tissues such as brain and pituitary (Morash et al 1999), mouse testis (Herrid et al 2008), human semineferous tubuli and seminal plasma (Camina et al 2002) and even human spermatozoa (Aquila et al 2005). So, it increases the probability of paracrine and/or autocrine role of leptin, at least in these organs.…”
Section: Introductionmentioning
confidence: 96%